FORMAL STRUCTURE AND POLYPHONIC TECHNIQUE IN ZOLTÁN KODÁLY’S “SEVEN EASY CHORAL PIECES FOR CHILDREN" - Gabriela COCA (Studia Universitatis Babeş-Bolyai. Musica)
The aim of the paper hereby is the analysis of Zoltán Kodály’s Seven Easy Choral Pieces for Children, an aim set out of mere curiosity. Theoretically I analyzed these choral pieces years ago during my classes of score transcription for choirs. I noticed already then that despite their simplicity and absolute clearness these pieces are very logical and masterly elaborated. Zoltán Kodály composed his Seven Easy Choral Pieces for Children in 1936. His thoughtfulness and precision is proven also by the fact that he wrote the year of composition to every piece, although these small pieces belong to the same cycle.